(untitled) (Boletin Médico de Postgrado, 2020)
Renal cell cancer (RCC) is the most common solid lesion in the kidney and accounts for approximately 90% of malignant renal tumors. There is a 1.5:1 male predominance and the highest incidence occurs between 60 and 70 years of age. RCC represents 2%-3% of all cancers and its highest incidence occurs in western countries. We report a rare case of a female patient of 35 years of age who has had pain free hematuria for two days. A contrasted abdominal/pelvic CT revealed a lesion of approximately 15 x 12 x 10 cm with neoproliferative appearance and heterogeneous features of hypo and hyperdensity of 40 uH, with neovascularization and contrast enhancement, compromising the middle and lower calyx of the left kidney extensive to renal pelvis. A left radical nephrectomy was performed. Histopathological study revealed a well-differentiated low grade clear cell carcinoma, with free margins and lymph nodes without metastasis. The patient has a satisfactory evolution and is awaiting adjuvant treatment. Due to the fact that the patient is a young adult, the urologist should be able to make the diagnosis as soon as possible.